PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN KUALITAS PELAYANAN TERHADAP MINAT MUZAKI MEMBAYAR ZAKAT - Nahdliatul Amalia; Tika Widiastuti (Universitas Airlangga, 2019)
This study aims to determine the effect of accountability, transparency, and service quality on the interest of muzaki (study at zakat institutionsSurabaya). This study uses a quantitative approach with multiple linear regression analysis. The population in this study is all muzaki registered at zakat institutions in Surabaya. The sampling technique using convenience sampling. This study uses 6 (six) zakat institutions that have been selected by taking a sample of 120 muzaki. Primary data collection in this study used a questionnaire. Based on the results of the study show that accountability, transparency, and service qualitypartially have a positive and significant effect on the interest of muzaki to paying zakat. Accountability, transparency, and service qualitysimultaneously have a positive and significant effect on the interest of muzaki to paying zakat.Keywords: Accountability, Transparency, Service Quality, Interest, Zakat, Zakat InstitutionREFFERENCESAr Rahman, Muhammad .A.M. (2003).1001 masalah zakat dan solusinya. Jakarta: Pustaka Cerdas Zakat.Hadi, Sutrisno. (1991). Analisis Butir Untuk Instrumen Angket, Tes, dan Skala Nilai. Yogyakarta: FP UGM.Hafidhuddin, Didin. (2002). Zakat Dalam Perekonomian Modern. Jakarta: Gema Insani Press.Jaelani, A.F..(2006). Membuka Pintu Rezeki.Depok: Gema Insani.Lucas, D.B & Britt, S.H. 2003.Advertising Psychology and Research. New York: Mc Graw-Hill.Nurhayati, Sri dan Wasilah. (2009). Akuntansi Syariah di Indonesia.Edisi 2. Jakarta: Salemba Empat.Permono, Sjechul Hadi. (2005). Formula Zakat Menuju Kesejahteraan Sosial. Surabaya: CV. Aulia Surabaya.Sangadji, Etta Mamang dan Sopiah.(2013). Perilaku Konsumen. Yogyakarta: CV ANDI OFFSET.Tapanje, A.M.A. (2009). Corporate Governance From The Islamic Perspective: A Comparative Analysis With OECD Principles,Critical Perspectives On Accounting. Vol 20.Undang-undang Nomor 38 Tahun 1999 Tentang Pengelolaan Zakat.